Supplementary material for Potential source areas for atmospheric lead reaching Ny-Ålesund from 2010 to 2018 - Bazzano, Andrea; Bertinetti, Stefano; Ardini, Francisco; Cappelletti, David; Grotti, Marco (Zenodo, 2021)
Supplementary material for Potential source areas for atmospheric lead reaching Ny-Ålesund from 2010 to 2018. This repository contains source code and additional supplementary materials from our manuscript, "Supplementary material for Potential source areas for atmospheric lead reaching Ny-Ålesund from 2010 to 2018". This is the version of the supplementary material submitted to Atmosphere, MDPI.